Rapid humidity changes across the Northern South China Sea during the last ~40 kyrs - Kaboth-Bahr, Stefanie; Bahr, André; Yamoah, Kweku A.; Chuang, Chih-Kai; Li, Hong-Chun; Su, Chih-Chieh; Wei, Kuo-Yen (Marine geology, 2021)
A key aspect of East Asian climate is its summer monsoonal system which influences nearly one-third of the world's population. Recent results indicate that the primary response of the East Asian summer monsoon (EASM) to anthropogenic forced climate warming may be a shift in geographical range instead of an intensity change, which would lead to spatial coexistence of floods and droughts over southeastern Asia. The predicted EASM variability in the future has made it paramount to study its past changes and the associated tempo-spatial pattern of aridity and humidity in its purview. In order to decipher past changes in EASM, we applied a multi-proxy geochemical approach to the sediment core ORI-891-16-P1 located in the northern South China Sea. The position of this sediment core on top of a seamount makes it uniquely sensitive to changes in the terrigenous input into northern South China Sea unbiased by sea level-induced downslope transport processes. Utilizing the ln(Ti/Ca) ratio throughout the sediment sequence we trace terrigenous influx changes reflecting EASM prevalence during the last ~40 kyrs. Based on the comparison of our results to previous studies we infer that the Last Glacial Maximum (LGM; ~ 20 ka BP) was characterized by a steep N-S humidity gradient. This spatial pattern was in line with a southward shift or contraction of the summer monsoonal trough of 10-15° from its current position toward the centre of the South China Sea. Superimposed on orbital time scale fluctuations we also find strong indication of millennial-scale variability related to Heinrich Stadials. The impact of Heinrich Stadials on the EASM seems amplified during insolation minima, while high summer insolation seems to buffer the monsoonal system to such perturbations. We infer that (i) the humidity-aridity distribution during the LGM mimics predictions of the proposed future EASM configuration, and (ii) that the sensitivity of the EASM to weakening in the Atlantic Meridional Overturning Circulation is the strongest since the last glacial.